(untitled) (Conferencea, 2022)
The primary aim of this article is to demonstrate the importance of advanced technologies in teaching and acquiring the English languages. “A new age demands a new paradigm” – Walter McKenzie. People even couldn’t imagine about technological changes in a sphere of teaching 100 years ago. Although English is a native language of British, it has been established as a second language in many countries, namely in India, Nigeria, Ghana and so on. Thus there is a high percentage of demand for acquiring this language all over the world.